Selective Interactions of Mouse Melanocortin Receptor Accessory Proteins with Somatostatin Receptors - Meng Wang; Jing Xu; Xiao-Wei Lei; Cong Zhang; Shang-Yun Liu; Li-Na Jin; Chao Zhang (Cells, 2022)
Somatostatin receptors (SSTRs) are G protein-coupled receptors (GPCRs) known to regulate exocrine secretion, neurotransmission, and inhibit endogenous cell proliferation. SSTR subtypes (SSTR1-SSTR5) exhibit homo- or heterodimerization with unique signaling characteristics. Melanocortin receptor accessory protein 1 (MRAP1) functions as an allosteric modulator of melanocortin receptors and some other GPCRs. In this study, we investigated the differential interaction of MRAP1 and SSTRs and examined the pharmacological modulation of MRAP1 on mouse SSTR2/SSTR3 and SSTR2/SSTR5 heterodimerization in vitro. Our results show that the mouse SSTR2 forms heterodimers with SSTR3 and SSTR5 and that MRAP1 selectively interacts with SSTR3 and SSTR5 but not SSTR2. The interactive binding sites of SSTR2/SSTR3 or SSTR2/SSTR5 with MRAP1 locate on SSTR3 and SSTR5 but not SSTR2. The binding sites of MRAP1 to SSTR3 are extensive, while the ones of SSTR5 are restricted on transmembrane region six and seven. The heterodimerization of mouse SSTR2, SSTR3, and SSTR5 can be modulated by binding protein in addition to an agonist. Upregulation of extracellular signal-regulated kinases phosphorylation, p27Kip1, and increased cell growth inhibition with the co-expression of SSTR2/SSTR3 or SSTR2/SSTR5 with MRAP1 suggest a regulatory effect of MRAP1 on anti-proliferative response of two SSTR heterodimers. Taken together, these results provide a new insight of MRAP1 on the maintenance and regulation of mouse SSTR dimers which might be helpful to better understand the molecular mechanism involving SSTRs in tumor biology or other human disorders.